2016
DOI: 10.1371/journal.pone.0153687
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Intervention Attenuates the Cafeteria Diet-Induced Impairment of Stress-Coping Strategies in Young Adult Female Rats

Abstract: The current prevalence of diet-induced overweight and obesity in adolescents and adults is continuously growing. Although the detrimental biochemical and metabolic consequences of obesity are widely studied, its impact on stress-coping behavior and its interaction with specific exercise doses (in terms of intensity, duration and frequency) need further investigation. To this aim, we fed adolescent rats either an obesogenic diet (cafeteria diet, CAF) or standard chow (ST). Each group was subdivided into four su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 75 publications
1
20
0
1
Order By: Relevance
“…We have previously shown in Cigarroa et al . [ 13 ] that CAF-fed rats have higher amounts of triglycerides in their serum than animals fed ST, and this increase gradually drops with exercise until triglycerides nearly return to ST-fed levels in the TMH-CAF group ( Fig 1A ). CAF feeding also had significant effects on the remaining dyslipidemic variables (p<0.05, two-way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown in Cigarroa et al . [ 13 ] that CAF-fed rats have higher amounts of triglycerides in their serum than animals fed ST, and this increase gradually drops with exercise until triglycerides nearly return to ST-fed levels in the TMH-CAF group ( Fig 1A ). CAF feeding also had significant effects on the remaining dyslipidemic variables (p<0.05, two-way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
“…Training sessions were performed as previously described [ 13 ]. Briefly, the rats were trained on a treadmill 5 days per week for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrient composition of CAF used herein as well as the caloric breakdown were recently described by Cigarroa et al . 29 . Body weight was recorded twice a week, and food intake was documented every 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, aerobic exercise could attenuate mass gain, likely due to increased energy expenditure, resulting in a negative energy balance and, consequently, a reduction of mass gain. Such an outcome was observed in an experimental study by Cigarroa et al [35], which demonstrated that a treadmill intervention could counterbalance the mass gain of animals fed a cafeteria diet.…”
Section: Discussionmentioning
confidence: 74%